Women Riding a Two - Wheeler in Chennai : Has the Perception Changed ? A Perspective - Srinath, Ramnath (Prabandhan: Indian Journal of Management, 2018)
Riding two wheelers by Indian women is still not common - it is more a compulsion than choice. Physical inability to move around more easily, a traditional outlook in society- joint families are the conventional impediments that affect the purchase decision of two wheelers among Indian women. Initiatives have been taken by a few two-wheeler marketing companies to break the myth of an almost impossible task through innovative designs, targeting women riders too. A large market is untapped as indicated by their survey; while little is happening. Under this backdrop, this study is an initiative to convert the compulsion into choice after studying the mass opinions based on a primary field survey. Three groups of women participated in the study as samples and the purposive sampling method was used; the women respondents were categorized into three categories: namely working women, students, and homemakers. The study indicated interesting results, signaling choice disparity. The impact is yet to set in, in a big way, and it is rather a challenge for marketing companies to convert the chance into choice in future by preparing appropriate plans to target more women users and persuade them to use two wheelers as a convenient mode of transport.